ISOLTRAP mass measurements of exotic nuclides at [delta]m/m=10−8 - Blaum, Klaus; Kluge, Heinz-Jürgen (Nuclear physics. B, Particle physics, 2005)
The ISOLTRAP experiment at the ISOLDE facility at CERN is a Penning trap mass spectrometer for on-line mass measurements on short-lived radionuclides. It allows the determination of atomic masses of exotic nuclides with a relative uncertainty of only 10−8. The results provide important information for, e.g., weak interaction studies and nuclear models. Recent ISOLTRAP investigations and applications of high-precision mass measurements are discussed.
Im Titel wird Delta als griechischer Buchstabe dargestellt
Bei der Zahl 10 ist minus 8 hochgestellt
Gesehen am 04.03.2020